Observing the top energy asymmetry at the LHC - Berge, Stefan; Westhoff, Susanne (Physical review, 2017)
The top-antitop energy asymmetry is a promising observable of the charge asymmetry in jet-associated top-quark pair production at the LHC. We present new predictions of the energy asymmetry in proton-proton collisions at 13 TeV, including QCD corrections at the next-to-leading perturbative order. The effect of QCD corrections on the observable is moderate. With suitable phase-space cuts, the asymmetry can be enhanced at the cost of reducing the cross section. For instance, for a cross section of 1 pb after cuts, we predict an energy asymmetry of −6.5+0.1−0.2% at the next-to-leading order in QCD. We also investigate scale uncertainties and parton-shower effects, which partially cancel in the normalized asymmetry. Our results provide a sound basis for a measurement of the energy asymmetry at the LHC during run II.
Gesehen am 24.05.2017